Respuestas
Respuesta dada por:
1
Base = b
Altura = a
a × b = 12 (1)
2a + 2b = 16 (2)
De (1) despejas a
a × b = 12
a = 12/b (3)
Reemplazas en (2)
2a + 2b = 16
2×12/b + 2b = 16
24/b + 2b. = 16
(24+ 2b²) /b = 16
24+ 2b² = 16b
2b² - 16b + 24 = 0 //entre 2
b² - 8b + 12 = 0
(b - 6) (b - 2) = 0
b - 6 = 0 == b = 6cm
b - 2 = 0 == b = 2 cm
Reemplazas b = 6 en (3)
a = 12/b = a = 12/6 =>a = 2 cm
Base = 6 cm
Altura = 2cm
Altura = a
a × b = 12 (1)
2a + 2b = 16 (2)
De (1) despejas a
a × b = 12
a = 12/b (3)
Reemplazas en (2)
2a + 2b = 16
2×12/b + 2b = 16
24/b + 2b. = 16
(24+ 2b²) /b = 16
24+ 2b² = 16b
2b² - 16b + 24 = 0 //entre 2
b² - 8b + 12 = 0
(b - 6) (b - 2) = 0
b - 6 = 0 == b = 6cm
b - 2 = 0 == b = 2 cm
Reemplazas b = 6 en (3)
a = 12/b = a = 12/6 =>a = 2 cm
Base = 6 cm
Altura = 2cm
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años